Design and optimization of optical fiber networks for 5G and beyond - Nabeil A. Abujnah (African Journal of Advanced Pure and Applied Sciences, 2024)
As the demand for high-speed, reliable connectivity continues to grow, 5G networks have emerged as an important infrastructure, pushing the boundaries of data transmission and connectivity. Optical fiber networks are critical to achieving low latency, high bandwidth, and the strong potential needed for future technologies such as 5G and 6G. This paper looks at design and optimization strategies for optical fiber networks tailored to 5G’s unique needs, addressing key challenges such as scalability, reliability, interference, and energy efficiency. Through a comprehensive analysis of network topologies, routing techniques, and emerging technologies, including dense wavelength division multiplexing (DWDM) and the role of artificial intelligence (AI) in network management, this research highlights effective solutions to enhance optical fiber performance. Real-world case studies further highlight the human impact of improved fiber networks, showing how improved connectivity promotes economic development, social inclusion, and technological innovation. By exploring both current methods and future directions, this study provides actionable insights for advancing optical fiber networks in the 5G era and beyond, setting the stage for a smoothly connected future.